2019
DOI: 10.1097/ijg.0000000000001280
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Optical Coherence Tomography Imaging For Glaucoma Associated With Boston Keratoprosthesis Type I and II

Abstract: Precis: Three-dimensional (3D) spectral domain optical coherence tomography (OCT) volume scans of the optic nerve head (ONH) and the peripapillary area are useful in the management of glaucoma in patients with a type I or II Boston Keratoprosthesis (KPro). Purpose: The purpose of this study was to report the use of spectral domain OCT in the management of glaucoma in patients with a type I or II Boston KPro. Materials and Methods: This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Retinal nerve fiber layer (RNFL) thinning measured using SD-OCT can be indicative of glaucoma progression. In a prospective study of 16 KPro eyes with penetrating keratoplasty eyes as controls, high test-retest reliability and repeatability were observed in SD-OCT RNFL thickness measurements in KPro eyes [30 & ], although another study noted higher rates of segmentation error of the RNFL in KPro eyes [31].…”
Section: Other Surveillance Methods In Penetrating Keratoplasty and K...mentioning
confidence: 99%
“…Retinal nerve fiber layer (RNFL) thinning measured using SD-OCT can be indicative of glaucoma progression. In a prospective study of 16 KPro eyes with penetrating keratoplasty eyes as controls, high test-retest reliability and repeatability were observed in SD-OCT RNFL thickness measurements in KPro eyes [30 & ], although another study noted higher rates of segmentation error of the RNFL in KPro eyes [31].…”
Section: Other Surveillance Methods In Penetrating Keratoplasty and K...mentioning
confidence: 99%
“…Nonpassopon et al gathered information from several Boston KPro clinical trials and found 20.2–40% of eyes had an increase in intraocular pressure (IOP), 14–36% developed de-novo glaucoma, and 13–33% had progression of previously present glaucoma ( 42 ). These results are primarily due to the device being unable to detect elevated IOP early with standard tonometry techniques due to the rigidity of the KPro device ( 68 ). Therefore, a potential solution has been introduced by integrating a micro-optomechanical pressure sensor into the Boston KPro device.…”
Section: Hard Keratoprosthesesmentioning
confidence: 99%
“…It was concluded that RPM formation shortened the optical cavity and caused an artificial IOP increase ( 69 ). Another alternative is to use three-dimensional (3D) spectral-domain optical coherence tomography (OCT) to enhance the evaluation of KPro patients with glaucoma ( 68 ).…”
Section: Hard Keratoprosthesesmentioning
confidence: 99%
“…85 In addition to better IOP monitoring, several publications advocate the use of anterior segment optical coherence tomography (OCT), 3D-optic nerve OCT, optic nerve head imaging and digital planimetric analysis of Goldman visual field, to better assess structural and functional glaucomatous change after BKPro implantation. 62,63,86 Many modalities are also postulated to prevent other BKPro-related complications. The lack of biointegration has long been considered one of the greatest BKPro downsides leading to a continuous risk of intraocular infection.…”
Section: Future Of Bkpromentioning
confidence: 99%